THE ROLE OF ABSOLUTE RETICULOCYTE COUNTS IN EVALUATION OF PANCYTOPENIA: A CROSS-SECTIONAL STUDY, BIHAR, INDIA. - Rawi Agrawal; Kaushal Kumar; Satish Kumar; Vijayanand Choudhary (Student's Journal of Health Research, 2023)
Background Hematological conditions like pancytopenia are widespread in our lab. Diagnosis and therapy of pancytopenia require etiology analysis. Most pancytopenia causes are determined by the Absolute Reticulocyte Count (ARC), which has been neglected. The aim of this study is to determine the importance of the Absolute Reticulocyte Count (ARC) in assessing the etiology of pancytopenia, with a focus on its role in distinguishing between different causes of this hematological condition. Materials and Methods The study was conducted in a tertiary health care institution in Bihar, India. Over the course of 1 year (April 2021 to March 2022), a descriptive cross-sectional study was carried out. Complete blood counts (CBC), reticulocyte count including ARC and peripheral blood smear (PBS) examination were performed in all cases of pancytopenia. Serum ferritin, Serum vitamin B12 level and serum folate were also estimated. Bone marrow examination was done in all cases. Results A total of 200 pancytopenia cases were assessed, and the findings were recorded. In cases of aplastic anemia, ARC was found to be <25x109 /L, in megaloblastic anemia ARC was found to be 25-50x109 /L and ARC >100x109 /L was seen in neoplastic disorders. Lower ARC values were associated with conditions like aplastic anemia, while higher ARC values were indicative of acute leukemia and metastatic deposits, making ARC a valuable diagnostic tool. Conclusion It was concluded that ARC is crucial in distinguishing between different causes of pancytopenia, and it must be a regular part of work-up to prevent needless invasive bone marrow examinations in cases of pancytopenia. Recommendation This study suggests that pancytopenia patients be routinely assessed with Absolute Reticulocyte Count (ARC). ARC helps identify pancytopenia etiologies, preventing needless bone marrow exams. Pancytopenia diagnosis and treatment can be improved by adding ARC to diagnostic techniques.